The Syntax of Colophons: A Comparative Study across Pothi Manuscripts (Studies in Manuscript Cultures, 2022)
The present volume focuses on the colophons found in several pothi manuscripts from Central, South and South East Asia. Its contributions discuss the colophons’ defining features, thus exposing their ‘syntax’, focusing particularly on the tracing of recurring patterns. The information extrapolated from colophons is further analysed to obtain a better understanding of these distinct manuscript cultures.